Use of brodalumab for the treatment of chronic plaque psoriasis: a one-year real-life study in the Lazio region, Italy. (2nd September 2021) - Galluzzo, M; Caldarola, G; De Simone, C; Bernardini, N; Moretta, G; Pallotta, S; Botti, E; Campione, E; Pirro, F; Potenza, C.; Bianchi, L; Peris, K
ABSTRACT: Background : Information is limited from real-life studies evaluating the efficacy and safety of brodalumab.Research design and methods : In this real-life study, we retrospectively examined a database of 90 patients with moderate-to-severe psoriasis treated with brodalumab (210 mg, s.c.) and followed for 1 year. Disease severity and treatment response were assessed by the Psoriasis Area and Severity Index (PASI) at baseline and after 4, 12, 24, 36, and 48 weeks. Predictors of a PASI response were evaluated by logistic regression.Results : After 48 weeks, 92.2% of patients (mean age 50.2 ± 15 years) treated with brodalumab achieved a PASI score of <3. PASI score decreased from 17.4 ± 10.3 at baseline to 1.7 ± 3.9 and 1.4 ± 3.7 at 12 and 24 weeks, and PASI 75, 90, and 100 response was achieved in 87.3%, 81.8%, and 72.7% of patients, respectively, at 48 weeks. Univariate regression revealed that previous exposure to anti-IL17A treatment was associated with poorer PASI response between 36 and 48 weeks. In difficult-to-treat cases previously having failed with other biologics, brodalumab significantly improved outcome, leading to complete remission.Conclusion : Brodalumab was observed to be effective and safe in patients with moderate-to-severe chronic psoriasis in a real-world setting.